Wetland inventory, key drivers of change and their socioeconomic and environmental implications in Ethiopia - Workiyie Worie Assefa; Belachew Getnet Eneyew (Ecological Indicators)
Efforts have been made to estimate the total areas of wetlands coverage and their distribution in Ethiopia. However, their abundance and distribution throughout the country remain unclear. This study, thus, aimed to assess the status and dynamics of wetlands coverage in Ethiopia. Besides, the drivers of wetland degradation and its implications on water supply, local people’s livelihoods, climate change, and biodiversity. Global Land Analysis and Discovery (GLAD), and Global Wetland Database were used to analyze abundance distribution and dynamics of wetlands in Ethiopia. The documentary sources (journal articles and books) were used to assess the driving factors of wetland degradation and the implications of wetland loss. The global wetland dataset analysis findings indicated that the total area coverage of the country’s wetlands in 2020 was 26,424.72 km2 representing 2.02 % of the country’s total area coverage. Of which, 16,501.96 km2 was covered with wetlands and 9,922.76 km2 was covered with open-water (lakes and artificial reservoirs). The analysis of the LULC pattern indicated that the land coverage of open-water had increased by 20 % within 20 years (2000 to 2020), which was contradictory to the decline of 9 % of the wetland coverage. The construction of dams or reservoirs for hydroelectric supply, irrigation, and water supply for large towns or cities is the principal factor for increasing open-water coverage. On the contrary, cultivated land expansion, increasing the application of agrochemicals, overgrazing, lack of standalone wetland policy, sedimentation, climate change, excessive extraction of water for irrigation and other purposes, and urban expansion contribute to the degradation of wetlands. Considerable loss of wetlands will have implications on water supply for various uses, local level livelihoods, local climate regulation, carbon emission, and aquatic biodiversity.